2017
DOI: 10.1007/s40261-017-0612-2
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Inhaled Medications and its Effect on Healthcare Utilization and Costs Among High-Grade Chronic Obstructive Pulmonary Disease Patients

Abstract: Adherence reduces healthcare utilization and costs, so adherence is not only clinically effective but also economically efficient. However, less than one-quarter of this population remained adherent over the 4-year period, suggesting that strategies are needed to improve adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Thus, education of the importance of inhalers to GP is essential for increasing inhaler prescription. Education of patients is also important, as adherence rates are low . Educational programmes for patients improve awareness of the importance of inhalers .…”
Section: Low Rate Of Use Of Inhalers and High Rate Of Use Of Oral Medmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, education of the importance of inhalers to GP is essential for increasing inhaler prescription. Education of patients is also important, as adherence rates are low . Educational programmes for patients improve awareness of the importance of inhalers .…”
Section: Low Rate Of Use Of Inhalers and High Rate Of Use Of Oral Medmentioning
confidence: 99%
“…Education of patients is also important, as adherence rates are low. 9 Educational programmes for patients improve awareness of the importance of inhalers. 4 Government-level interventions can also be effective.…”
Section: Low Rate Of Use Of Inhalers and High Rate Of Use Of Oral Medmentioning
confidence: 99%
“…98 This is in contrast to the significant association the authors found between adherence and lower intensive care unit use and healthcare costs within the same population. 98 Given the acute nature of ED visits, there is evidence that a wide range of clinical, psychological and social factors are associated with ED visits in adults, 99 and studies assessing adherence need to adjust for a range of confounding variables. These confounders can also be time-varying, and only 1 of the studies included in our ED meta-analysis (Figure 3) separated the time period for outcome measurement from the exposure assessment period.…”
Section: Discussionmentioning
confidence: 74%
“…The association between non‐adherence and ED visits is not clear in the literature. In fact, a recent Korean study found that after 2 years of being adherent, high‐grade COPD patients had an increased likelihood of having ED visits in comparison to non‐adherent patients . This is in contrast to the significant association the authors found between adherence and lower intensive care unit use and healthcare costs within the same population .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation